La responsabilité civile délictuelle des municipalités en matière de combat des incendies - McNicoll, Micheline (Les Cahiers de droit, 1983)
The delictual responsibility of a municipality for offences and quasi-offences committed by its fire department or brigade has been clearly acknowledged by Quebec Courts. This position, which some consider anachronistic, is the result of a long evolution whereby the private law rules of civil responsibility were gradually introduced in the normally closed field of public law. The following article is a study of the most recent developments in this area, as well as an attempt by the author to ascertain the applicability of the civil law to the field of municipal delictual responsibility in general.